E-learning - a Support Tool for Teaching and Learning: a Manipal University Initiative - Rao, Mahabaleshwara; Mudhol, Mahesh V.; Shivananda Bhat, K. (Journal of Information and Knowledge, 2013)
The current trend is ‘e’ with everything: e-commerce, e-science and e-learning. The world is embarking on a new age, an age of e-learning. Electronic education is rapidly becoming a fixture in higher education. e- Learning encompasses concepts such as ‘virtual universities’ and networked and online learning. It is almost two decades now that various schemes and programs have been launched both at government and non-governmental levels to develop ICT (Information and Communication Technology) skills in teachers. Various universities in India have designed specific courses for this purpose. Organizations like the NCERT, UGC, NCTE etc. have been launching schemes to enhance the ICT skills of teachers. However, in a big country like India with millions of teachers at different levels, it is indeed difficult to produce ICT-enabled teachers on a large scale within a short period. The problems are complex and issues are numerous. In this paper, we present an overview of e-learning initiative at Manipal University, Manipal.